Meta-Analysis: The Effect of Lactation Education by Midwives on Exclusive Breastfeeding Behavior in Mothers and Pregnant Women - Amanda Kesli Ramadhani; Akbar Suryananda (Journal of Health Promotion and Behavior, 2022)
Background: Exclusive breastfeeding has a good impact on the baby's growth and development. Therefore, the role of health workers, especially midwives, is needed to provide an education about the importance of exclusive breastfeeding for babies. The purpose of this study was to determine the effect of lactation education conducted by midwives related to exclusive breastfeeding behavior for mothers and pregnant women.Subjects and Method: This study is a meta-analysis study with Population: Mothers and pregnant women, Intervention: lactation education by midwives, Comparation: without midwife lactation education and Output: Exclusive breastfeeding behavior. The article search process is carried out through the Pubmed web search engine and is a research article published from 2017-2022. The articles obtained will be filtered using the stages according to the PRISMA flow diagram.Results: A total of 9 articles used in this study were reviewed and met the requirements for a meta-analysis, the research conducted in these articles was carried out in various countries such as Indonesia, Bangladesh, Euthiopia, and Spain. Where from the meta-analysis of 9 cross-sectional articles, it is known that there is an influence between lactation education by midwives and exclusive breastfeeding behavior for mothers and pregnant women (aOR= 1.60; 95% CI= 1.37 to 1.88; p= 0.008).Conclusion: Lactation education by midwives increases exclusive breastfeeding behavior for mothers and pregnant women.Keywords: lactation education, exclusive breastfeeding, midwives, mothers, pregnant women, meta-analysis.Correspondence:Amanda Kesli Ramadhani. Universitas Muhammadiyah Surakarta, Jl. A. Yani Mendungan, Kartasura, Sukoharjo, Central Java. Email: amandakesly@yahoo.com. Mobile: 085692832776.Journal of Health Promotion and Behavior (2022), 07(02): 86-96DOI: https://doi.org/10.26911/thejhpb.2021.07.02.01